PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK USIA DINI MELALUI METODE BERMAIN EGRANG BATOK KELAPA DI RA-ALHIDAYAH MEDAN - Hasnah Siahaan; Ibrahim Gultom; Masganti Sitorus (JURNAL TEMATIK, 2019)
This study aims to look at the gross motor improvement of early childhood byusing the method of playing coconut shell stilts. This research is a classroom actionresearch. In cycle I it was found that gross motor skills of early childhood 68% ofchildren who were able to classically or 17 children who completed learning and 8 morechildren who were not yet completed, had not yet achieved the predetermined successcriteria of 80% of children overall, caused by : lack of teachers 'ability to direct earlychildhood in playing coconut shells, lack of teachers' ability to manage time and childrenlack enthusiasm to use coconut shells. In the second cycle, improvements were made,namely: giving examples according to the steps to play coconut shell stilts, the resultsobtained in this second cycle were 92% of early childhood or 23 children were able toplay coconut shells in a classical manner. As a result the child was seen active in theprocess of motor learning in the RA Al-Hidayah group B Medan. The impact can be seenin mastery of motion and ultimately can improve the gross motor skills of children. Theimplication of this research is that teachers in RA Al-Hidayah Medan are expected to usecoconut shells as a method to improve gross motor skills of early childhood.